Help Your Dragon Cope with Trauma: A Cute Children Story to Help Kids Understand and Overcome Traumatic Events. - Herman, Steve, (Children's author) ([Place of publication not identified] : DG Books Publishing, 2019)
Having a pet dragon is so much fun! He can sit, roll over, and play$1! = (BHe can candle a birthday cake, lit a campfire, or so many other cool things$1! = (BBut what if your dragon experienced a traumatic event? What if he$1 (Bs constantly having bad dreams about the terrible thing he experienced? What if he wasn$1 (Bt able to rest well, and telling you his tummy hurts? What if he tried to run away but couldn$1 (Bt escape from his thoughts of the awful thing that happened? What if he didn$1 (Bt want to share with you or to talk about the terrible thing he saw? What if his broken heart can$1 (Bt seem to heal, and you$1 (Bre really concerned? What should you do? You help him talk about and understand the experience. You give him practical advice and activities to overcome his fear. You help him understand his feelings and you teach him that life goes on, and most of it is good, and so much, much more$1! = (BBut How? Get this book and learn how! Fun, cute, and entertaining with beautiful illustrations WITHOUT being scary and specific about traumatic events , this is a must have book for children, parents and teachers to teach kids to understand and overcome traumatic events that they might experience. GET THIS BOOK NOW AND ENJOY!s
New Kids Book Winter 2023.
Keywords: Dragons; Psychological trauma